Validity and Reliability of the Self-Administered Timed Up and Go Test in Assessing Fall Risk in Community-Dwelling Older Adults - Magda Reis; Maria Teixeira; Carlota Carvão; Anabela Correia Martins (Geriatrics)
Objectives: This study aimed to evaluate the validity and reliability of the self-administered Timed Up and Go (TUG) test—a gold standard for fall risk screening—by comparing it to the traditional face-to-face assessment conducted by a physiotherapist. Methods: A total of 37 community-dwelling adults—mean age 61.78 ± 6.88, 73% female—who took part in fall risk screening actions in the central region of Portugal were assessed. The protocol included sociodemographic and history of falls questions, the Self-Efficacy for Exercise questionnaire, the Activities and Participation Profile Related to Mobility (PAPM), and three functional tests, namely the 10-Metre Walking Speed (10-MWS), TUG, and 30 Seconds Sit to Stand (30 s STS) tests. Within an interval of 18–24 h after the face-to-face moment, the participants were instructed to self-administer the TUG test at home. The validity and reliability of self-administered TUG test were examined using the limits of agreement, clinically acceptable limit, intra-class correlation coefficients (ICCs), paired t-tests, and Pearson’s coefficient correlation (r). Results: The limits of agreement for self-administered assessment were within the clinically acceptable limits. The average result of the face-to-face TUG test and the self-administered TUG test was 7.47 ± 2.45 and 7.57 ± 3.10 s, respectively. When comparing the two evaluations, they were strongly associated (r = 0.716, p < 0.001), with an excellent ICC of 0.82 (0.65–0.91), for a 95% confidence interval and significance level of 0.05 (p ≤ 0.05). Conclusions: The use of the self-administered TUG test for the screening of risk of fall, using low-cost technology, appears to be valid and reliable in community-dwelling adults aged 50 and above. Enabling older adults to perform the TUG test at home can empower them to take an active role in managing their health and ageing process, while also offering physiotherapists regular feedback for fall prevention.